Identifying strawberry DOF family transcription factors and their expressions in response to crown rot - Chun LUO; Yuyang HU; Bo SHU (Notulae Botanicae Horti Agrobotanici Cluj-Napoca, 2022)
Crown rot is one of the most destructive diseases of cultivated strawberry. The DOF family transcription factors, which involved in biotic stress, has not been studied in responding to strawberry crown rot. In this study, the DOFs of Fragaria × ananassa, F. iinumae, F. nilgerrensis, F. viridis, and F. vesca were characterized. One hundred and eighteen FaDOFs, twenty-two FiDOFs, twenty-three FnDOFs, twenty-five FviDOFs and thirty-seven FvDOFs were identified. Gene cluster analysis showed nearly seventy segmental duplication and seventeen tandem duplications for DOF family expansion in octaploid strawberry. In addition, 59 FaDOFs showed syntenic relationships with 32 AtDOFs, which were located on all F.×ananassa chromosomes except Fvb4-1 and Fvb4-2. Except for five DOFs of diploid strawberries had syntenic relationships to one FaDOF, most of them corresponded to multiple FaDOFs. Gene expression analysis revealed that 107 FaDOFs were expressed in crown, and most of them were downregulated by crown rot, while some FaDOFs such as FaDOF107, 12, 82, 91, 90 and 101 were upregulated, whose regulation was not always consistent with the cis-elements in their promoters. Together, these results provided a basis for further functional studies of the FaDOFs.